Effect of Planting Scheme on Growth and Productivity of Sweet Pepper "Lastochka" Variety - Mamayusupov Abbos Nurkabilovich; Buriev Khasan Chutbaevich (Journal of Geography, Regional Planning and Development, 2024)
In the article, the results of the research conducted in order to determine the effect of the planting scheme on the growth and productivity of the "Lastochka" variety of sweet pepper are presented with an in-depth scientific analysis.